International law and new wars - Chinkin, C. M.; Kaldor, Mary (Cambridge : Cambridge University Press, 2017)
International Law and New Wars examines how international law fails to address the contemporary experience of what are known as'new wars' - instances of armed conflict and violence in places such as Syria, Ukraine, Libya, Mali, the Democratic Republic of Congo and South Sudan. International law, largely constructed in the nineteenth and twentieth centuries, rests to a great extent on the outmoded concept of war drawn from European experience - inter-state clashes involving battles between regular and identifiable armed forces. The book shows how different approaches are associated with different interpretations of international law, and, in some cases, this has dangerously weakened the legal restraints on war established after 1945. It puts forward a practical case for what it defines as second generation human security and the implications this carries for international law.
Sovereignty and the authority to use force -- The relevance of international law -- Self-defence as a justification for war : the geo-political and war on terror models -- The humanitarian model for recourse to force -- How force is used -- Weapons --'Post-conflict' and governance -- The liberal peace : peacemaking, peacekeeping, and peacebuilding -- Justice and accountability -- Second generation human security -- What does human security require of international law?
Title from publisher's bibliographic system (viewed on 25 May 2017).
Keywords: War (International law); Jurisdiction (International law); Self-defense (International law); Humanitarian law; Reconciliation; Peace-building.; Security, International